The designing of customer management strategies using ICT tools in Pure Jatomi - Idzikowski, Wojciech; Cieśliński, Wojciech B. (Business Informatics, 2014)
The article presents the model of designing a customer management strategy using business ICT tools within a global sports association named Pure Jatomi. First, the basic categories essential for reaching a target of the project are explained (this section presents the results of literature analysis).Next, the general model of designing a customer management strategy (shown as a process map as well, developed on the basis of results of empirical investigation) is shown. Finally, ICT tools which enable acceleration of CLV growth (CLV = Customer Lifetime Value) are presented
Informatyka Ekonomiczna = Business Informatics, 2014, Nr 4 (34), s. 85-93
Keywords: customer value management; sports association; electronic communication; zarządzanie wartością klienta; organizacja sportowa; komunikacja elektroniczna